Teknologi Informasi dalam Membentuk Atribut Brand Equity Suatu Produk - Kristiana Asih Damayanti (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2004)
Product is known from its merk and Customer will choice and buy product which havegood and famous merk. For it, Company have to built good merk which can describe fromBrand Equity. Brand Equity has five atributes: Brand Assosiation, Brand Awareness,Perceived Quality, Brand Loyalty, and other atributes.This paper has a goal to make a model how Information Technology in built everyatributes of Brand Equity.Keyword: information technology, brand equity